ALTERNATIF INVESTASI BISNIS PERIKANAN TANGKAP PELAGIS DI KOTA AMBON - Hansje Matakupan; Johanis Hiariey; Agustinus Tupamahu; Mulyono S. Baskoro (Universitas Pattimura, 2019)
Investors can determine the appropriate investment alternatives in business, if they have calculated business feasibility based on investment criteria. Based on investment criteria, investors can determine investment alternatives appropriately. Research on investment alternatives in the pelagic capture fisheries business in Ambon City has been carried out to analyze investment feasibility and determine investment alternatives. The investment feasibility analysis method uses investment criteria namely Net Present Value (NPV), Net B/C Ratio, Gross B/C Ratio, Internal Rate of Return (IRR), Payback Period (PP), and Break Even Point (BEP) and determination of investment alternatives with the Analitycal Hierarchy Process (AHP) method. The results of the investment feasibility analysis of 7 types of pelagic fishing businesses in Ambon City, stated that all of them are worth invested. Analysis of investment alternatives with AHP based on investment criteria, determines that investors are best invest in the pelagic capture fisheries business in Ambon City with huhate (pole and line) with a CR value of 0.244 and purse seine with a CR value of 0.205.